Morphology of brood pouch formation in the pot-bellied seahorse Hippocampus abdominalis - Mari Kawaguchi; Ryohei Okubo; Akari Harada; Kazuki Miyasaka; Kensuke Takada; Junya Hiroi; Shigeki Yasumasu (Zoological Letters, 2017)
Abstract Background The reproductive strategies of vertebrates are diverse. Seahorses (Pisces: Syngnathidae) possess the unique characteristic of male pregnancy; i.e., males, not females, incubate embryos in a specialized structure called a ‘brood pouch’. The brood pouch is formed along the ventral midline of the tail. The lumen of the brood pouch is surrounded by loose connective tissue, called pseudoplacenta, and dermis. Results We visualized and evaluated the morphology of brood pouch formation in Hippocampus abdominalis to gain generalizable insights into this process in seahorses. First, we employed several staining methods to characterize the pseudoplacenta and dermis of the brood pouch of mature male seahorses. The pseudoplacenta is composed mainly of reticular fibers, while the dermis is composed mainly of collagenous fibers. Further observations showed that pouch formation is initiated by linear projections of epithelia on both ventrolateral sides of the body. These projections elongated toward the ventral midline, eventually fused together, and then formed a baggy structure composed of a single dermis layer with neither smooth muscle nor pseudoplacenta. Finally, the pseudoplacenta was formed, together with two layers of dermis and smooth muscle. Thus, a fully developed brood pouch was established. The morphology of the luminal epithelium also changed during pouch formation. We analyzed the localization of C-type lectins as markers; haCTL II was localized in both the outer and luminal epithelia of the brood pouch throughout development in the male seahorse, whereas haCTL IV, which was not detected in the early stage of seahorse development, became localized only in the luminal epithelium as development proceeded. Conclusions We categorized the processes of brood pouch formation during male seahorse development into three stages: (1) the early stage, characterized by formation of a baggy structure from the primordium; (2) the middle stage, characterized by the differentiation and establishment of brood pouch-specific tissues; and (3) the late stage, characterized by a fully formed pouch with developing blood vessels and a pouch fold ultimately capable of carrying and incubating embryos.